The midpoint of (x1,y1) and (x2,y2) is
![(\frac{x_1+x_2}{2},\frac{y_1+y_2}{2})](https://tex.z-dn.net/?f=%28%5Cfrac%7Bx_1%2Bx_2%7D%7B2%7D%2C%5Cfrac%7By_1%2By_2%7D%7B2%7D%29)
just average them
(4,1) and (-2,4)
the midpoint is
![(\frac{4-2}{2},\frac{1-4}{2})=(\frac{2}{2},\frac{-3}{2})=](https://tex.z-dn.net/?f=%28%5Cfrac%7B4-2%7D%7B2%7D%2C%5Cfrac%7B1-4%7D%7B2%7D%29%3D%28%5Cfrac%7B2%7D%7B2%7D%2C%5Cfrac%7B-3%7D%7B2%7D%29%3D)
(1,-1.5)
Answer:
Your correct answer is option C. -2 (9 + 32n)
Step-by-step explanation:
Solution:
Options are not given in the question
Given First degree expression:
-18-64n
= (-2)×9 + (-2)×32n
Take (-2) common, we get
= (-2)( 9+32n)
Therefore you get your answer of option C. -2(9+32n)
Answer:
X= 5
Explanation (Steps):
<u>Step 1: Simplify both sides of the equation.</u>
−3.4(x−2)=9.8−4x
(−3.4)(x)+(−3.4)(−2)=9.8+−4x(Distribute)
−3.4x+6.8=9.8+−4x
−3.4x+6.8=−4x+9.8
<u>Step 2: Add 4x to both sides.</u>
−3.4x+6.8+4x=−4x+9.8+4x
0.6x+6.8=9.8
<u>Step 3: Subtract 6.8 from both sides.</u>
0.6x+6.8−6.8=9.8−6.8
0.6x=3
<u>Step 4: Divide both sides by 0.6.</u>
0.6x0.6=3/0.6
x=5
Answer:
Larger number:
16
Smaller number
3
Step-by-step explanation:
Larger number: 16
Smaller number: 3
Explanation:
Suppose the larger number is
a
and the smaller number is
b
.
You solve the following system of equations:
a⋅b=48
a−13=b
Since b is a −13, you can plug that into a⋅b=48, so...a⋅(a−13)=48
a 2−13a=48
a2−13a−48=0
Factor the polynomial:
(a−16)(a+3)=0
a=16 or a=−3a is positive so a=16.
We can now solve for b by plugging in a, so...16−13=b3=b We have a=16 and b=3, meaning that the larger number is 16 and the smaller number is 3.